Positive School Climate Obstacles in the Schools of the First Cycle of Basic Education in Damascus from the Point of View of Teachers (Journal of Hama University, 2024)
The aim of the current research is to identify the obstacles of the positive school climate in the schools of the first cycle of basic education in Damascus from the point of view of teachers, and to identify the differences between them in the obstacles according to the variables (educational qualification, number of years of service, training courses followed). The sample consisted of(209)male and female teachers of the first cycle of basic education in the official schools of the city of Damascus .A questionnaire consisting of (39)items distributed within five distributed was used ,and the results showed :the obstacles to the positive school climate in the schools of the first cycle of basic education in the Damascus wear high from the point of view of teachers, and after (obstacles related to work pressures)came in the first place with a degree of agreement .Very high ,and it came after (obstacles related to human relations)with a medium degree of approval .It was found that there were statistically significant differences between the mean scores of the respondents answers to the questionnaire according to the educational qualification ,and according to the training courses used variable in favor of those who followed more training courses, while the differences were not statistically significant according to the number of years of service variable.
Keywords: obstacles positive school climate; Obstacles